A study of the flotation characteristics of a complex copper ore - Kalichini, Monica Shamvuse (Department of Chemical Engineering, 2016)
Kansanshi copper mine is situated in the north western province of Zambia. Weathering has given rise to a vertically zoned profile comprising leached, refractory, oxide, mixed and hypogene sulphide mineralisation. As a result of the mineral variations, the processing plant treats three distinct ore types; oxide, sulphide and mixed. The objective of this study was to investigate the floatability of a complex Kansanshi mixed copper ore comprising sulphide and oxide minerals with a view to achieving an optimal flotation performance in the treatment of the Kansanshi ore body. This required an in-depth analysis of the mineralogy of the feed as well as tailings samples after different flotation processes involving a range of reagent types and dosage procedures. The ore samples studied represented a high quality (HQ) ore dominated by sulphide minerals and low quality (LQ) ore dominated by oxide minerals. The quality of an ore at Kansanshi is defined by the acid soluble copper (ASCu) content of the ore, which is used as a proxy for oxide mineral content. An important finding in this study was that sulphide minerals are also prone to digestion during this analysis. Chalcopyrite was the major copper mineral in the HQ ore, constituting 3.9 %, but only 1.0 % of the LQ ore. LQ ore was dominated by chrysocolla, which constituted 3.8 % of the ore. The treatment of HQ ore with 30 g/t SIBX has shown that up to 90 % of the copper can be recovered from HQ ore. On the other hand, while 30 g/t SIBX was sufficient for chalcopyrite recovery in LQ ore, the tailings mineralogy after flotation with SIBX indicated that 78.8 % of the unrecovered copper in LQ ore was present as chrysocolla, 1.3 % as malachite and 5.8 % as chalcopyrite and therefore LQ ore required alternative flotation methods for the recovery of the oxide minerals. Comparison of slug sulphidisation and controlled potential sulphidisation (CPS) of LQ ore have shown that CPS performs better than slug sulphidisation only when the correct potential range and SIBX dosage after sulphdisation are used. Tailings mineralogy of LQ ore after sulphidisation showed a copper deportment of 0.1 % cuprite, 0.6 % malachite, 0.8 % chalcopyrite and 84.8 % chrysocolla, suggesting that all oxide copper minerals present in the LQ ore, except chrysocolla, are amenable to flotation using SIBX after sulphidisation. This observation was further verified through sulphidisation in a microflotation cell, which showed malachite recovery of 18.2 % compared to only 0.5 % of the chrysocolla. A techno-economic analysis comparing slug sulphidisation and CPS has indicated that CPS using a potential range of -300 to -400 mV performs better than slug sulphidisation from an economic stand point. At this potential, a NaHS:SIBX ratio of 7:1 was required, further highlighting the importance of using the correct collector dosage after sulphidisation.